REZERVATIA “VALEA LUI DAVID” (PANGEEA, 2025)
Protected areas are true shield of defense against natural disasters, providing space for flood drainage, stabilizing soil, thus avoiding landslides and protect us from the ravages of storms. Protected areas provide, in addition, conserve natural resources, without which we could get food and clean water and without which many of the communities could not survive.